2022
DOI: 10.3390/s22249876
|View full text |Cite
|
Sign up to set email alerts
|

Imputing Missing Data in Hourly Traffic Counts

Muhammad Awais Shafique

Abstract: Hourly traffic volumes, collected by automatic traffic recorders (ATRs), are of paramount importance since they are used to calculate average annual daily traffic (AADT) and design hourly volume (DHV). Hence, it is necessary to ensure the quality of the collected data. Unfortunately, ATRs malfunction occasionally, resulting in missing data, as well as unreliable counts. This naturally has an impact on the accuracy of the key parameters derived from the hourly counts. This study aims to solve this problem. ATR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…With regard to learning methods, predictive mean matching (PMM) based on multiple imputations by chained equations (MICE) has been looked into in [63]. A study done later on has then proceeded to compare variations of PMM methods, including MICE, Classification and Regression Trees (CART), Least Absolute Shrinkage and Selection Operator (LASSO), and random forest, with the result being the MissForest implementation of Random Forest being the best performer [11]. It is noteworthy that random forest is considered a machine learning algorithm, which shows why machine learning tends to be researched more compared to statistical methods, especially in recent years.…”
Section: A Statistical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to learning methods, predictive mean matching (PMM) based on multiple imputations by chained equations (MICE) has been looked into in [63]. A study done later on has then proceeded to compare variations of PMM methods, including MICE, Classification and Regression Trees (CART), Least Absolute Shrinkage and Selection Operator (LASSO), and random forest, with the result being the MissForest implementation of Random Forest being the best performer [11]. It is noteworthy that random forest is considered a machine learning algorithm, which shows why machine learning tends to be researched more compared to statistical methods, especially in recent years.…”
Section: A Statistical Methodsmentioning
confidence: 99%
“…Other missing data review papers, such as [10], have made a comparison between different missing traffic data imputation methods, namely prediction, interpolation, and statistical learning methods, and concluded that the PPCA-based (Probability Principle Component Analysis) methods perform the best overall in terms of accuracy and computational complexity. In addition, [11] has compared the performance of variations of other existing statistical methods such as linear regressions, Predicting Mean Matching (PMM), and mean imputation, while also comparing regression tree-based methods such as Classification and Regression Trees (CART) and Random Forest. The conclusion is that the random forest implementation performed the best.…”
Section: Similar Workmentioning
confidence: 99%
See 1 more Smart Citation